The governance of overseas surgical collaborations – BFIRST/BSSH. Issue 2 (February 2021) - Jemec, B.; Lam, W.; Hodgson, S.P.; Jones, J.W.M.; Eckersley, R.; Nyamulani, N.; Riaz, M.; Fell, M.; Nicholas, R.; Bhopal, R.; Mendis, Kapila; Khan, M.R. Karim; et al.
Summary: Clinical governance is the structured approach to maintaining and improving the quality of patient care and is a vital part of global surgery. BFIRST and BSSH closely collaborate with local doctors on a number of overseas projects, seeking to strengthen and develop local knowledge and skills, aiming for an independent local practice in reconstructive and upper limb surgery. Thoughts on essential requirements, improvements and pitfalls in the ethical approach to global collaboratives are presented.